An Analysis of factors affecting reading comprehension performance of Arabic ESL students using the Suffolk Reading Scale - Morris, Anne (2009)
The aim of this study was to examine the effectiveness of the Suffolk Reading Scale, a standardised multiple-choice paper and pencil test of reading comprehension, as a reliable method of assessing the reading ability of a group of ESL Arabic children aged between 9-10 years who were pupils at an international school in Dubai. The results indicated that the ESL Arabic children scored significantly lower than the comparison groups of non-Arabic ESL children and children with English L1 of the same age and studying in the same class. The study discusses the possible reasons for the difficulties experienced by the Arabic ESL children in decoding English text and attempts to conduct an error analysis by searching for any patterns of error that could be accounted for by interference from the Arabic L1 and other problems experienced by Arabic readers in decoding English text including problems with word recognition and spelling patterns, lack of phonemic awareness and insufficient reading strategies.